Teachers Rewards bagi Siswa SMA: Studi Indigenous Psychology - Hanifi, Rama Putra (Universitas Negeri Padang, 2023)
Abstract: Education that plays a significant role in human resources must implement effective learning method in a good teacher-student relationship. This research reveals the variety of rewards that effective on highschool students and its impacts felt by using an indigenous psychology approach. This research was conducted on 468 high school students in the city of Bukittinggi. This is a descriptive qualitative with an indigenous psychology approach, using an open-ended questionnaire with the stages of axial coding, preliminary coding, and categorization. The results suggest some teacher behaviors are perceived by students as a reward: (1) Honest response (2) Pleasant feedback (3) Appropriate treatment (4) Academic orientation (5) Teaching skills (6) good interpersonal skills (7) Academic laxity (8) Appreciation, the psychological impact students receive unconsciously from rewards is (1) Positive Emotions (2) Motivation (3) Affirmation (4) Adding skills (5) Positive feelings (6) Tolerance. The Results show teachers rewards by highschool students. Keywords: Rewards, indigenous psychology, highschool students. Abstrak: Pendidikan yang memiliki peran dalam sumber daya manusia harus mengimplementasikan metode pembelajaran yang efektif dalam relasi guru dan siswa. Penelitian ini mengungkapragam reward yang efektif diberikan pada siswa SMA dan jugadampak yang dirasakan dengan menggunakan pendekatan indigenous psychology. Penelitian ini dilakukan pada 468 siswaSMA di kota Bukittinggi. Penelitian ini menggunakan kualitatif deskriptif dengan pendekatan indigenous psychology,menggunakan open-ended questionnaire dengan tahapan analisisaxial coding, preliminary coding, dan categorization. Penelitian ini mendapatkan hasil yakni perlakuan guru yang dipersepsikan siswa sebagai reward adalah (1) Respon jujur (2) Feedback yang menyenangkan (3) Perlakuan yang tepat (4) Orientasi akademik (5) Keterampilan mengajar (6) Kemampuan interpersonal yang baik (7) Kelonggaran akademik (8) Apresiasi, dampak psikologis secara tidak sadar diterima siswa dari reward adalah (1) Emosi Positif (2) Motivasi (3) Afirmasi (4) Menambah keterampilan (5) Perasaan positif (6) Toleransi. Hasil ini menunjukkan Teachers Rewards bagi siswa SMA. Kata kunci: Reward, psikologi indigenous, siswa SMA.